Sharing the 'weight' of obesity management in primary care: integration of registered dietitian nutritionists to provide intensive behavioural therapy for obesity for Medicare patients. (20th February 2020) - Jacobs, Molly; Harris, Jordan; Craven, Kay; Sastre, Lauren
Abstract: Background: Clinical provision of intensive behavioral therapy for obesity (IBTO) has been a reimbursable treatment for obesity since 2012. However, gaps remain in the literature regarding its impact on patient outcomes. Objectives: The primary objective of this study was to examine the integration of registered dietitian nutritionist provided IBTO into a primary care setting and evaluate clinic outcomes for Medicare Part B beneficiaries. A secondary objective was to examine intensity of IBTO (quantity of IBTO visits) versus clinical outcomes and influence of socioeconomic factors. Methods: A case–control retrospective chart review was conducted at a rural, Academic Family Medicine Clinic in Eastern North Carolina for patients seen between 1 January 2016 and 1 January 2019. In order to be included in the treatment group, patients had to be female, white or black race, have Medicare insurance and a body mass index ≥ 30 kg/m 2 . Results: Mixed model analysis showed statistically significant improvements in clinical outcomes from IBTO treatment. Weight decreased by nearly 3 pounds, while body mass index was half a point lower. A1C was 0.1 units lower for IBTO patients, and they took prescription medication and average of 6 days less than the control group. Minorities and older respondents experienced smaller, all else constant, and annual fixed effects suggest that differentials widen over time. Conclusions: Registered dietitian nutritionist (RDN) provision of IBTO has demonstrated benefit in improving clinical outcomes including weight, A1C, and reduced medication duration (use) as demonstrated by the IBTO treatment group versus control. IBTO intensity was not predictive of success, and its impact was reduced with older and African American patients. IBTO is beneficial and can be delivered within the primary care setting by a RDN.